Treatment outcomes and associated factors among patients with multidrug-resistant tuberculosis in Ashanti Region, Ghana: a retrospective, cross-sectional study - Peter Agyei-Baffour; Victoria Panford; Emmanuel Kumah; Collins Kokuro; Prince Owusu Adoma; Michael Afari Baidoo; Adam Fusheini; Samuel Egyakwa Ankomah; Samuel Kofi Agyei (BMJ Open)
Objective Although several studies have assessed treatment outcomes of drug-susceptible tuberculosis (TB) in Ghana, very little has been done in the area of multidrug-resistant TB (MDR-TB). The aim of this study was to determine treatment outcomes and associated factors among patients treated for MDR-TB in the Ashanti Region, Ghana.Design A retrospective, cross-sectional analysis.Setting The study was conducted in the Ashanti Region, the second most populous region in Ghana. The regional MDR-TB register, which contains information on all patients with MDR-TB being treated at the various TB centres in the region, was analysed between February and May 2021.Participants The participants consisted of all registered patients with MDR-TB who were placed on treatment between 1 January 2015 and 31 December 2020. Patients were included in the analysis if their treatment outcome had been assigned. Patients with no record of treatment outcome were excluded from the study.Outcome measures The main outcome variable for the study was MDR-TB treatment outcome, standardised as ‘cured’, ‘treatment completed’, ‘treatment failure’, ‘died’ and ‘lost to follow-up’. A logistic regression model was fitted for factors associated with the outcome measure.Results Out of 159 patients included in the analysis, 86 (54.1%) were declared cured, 28 (17.6%) completed their treatment successfully, 6 (3.8%) were declared treatment failure, 12 (7.5%) were lost to follow-up and 27 (17.0%) died. The overall treatment success rate was 71.7%. Patients who were female (adjusted OR (AOR)=1.27, 95% CI: 1.18 to 1.39, p=0.023), younger (AOR=0.53, 95% CI: 0.19 to 2.11, p=0.012), had a higher level of education (AOR=1.12, 95% CI: 0.65 to 1.90, p=0.034), had a baseline body mass index of 18.5 kg/m2 or above (AOR=1.57, 95% CI: 1.23 to 2.47, p=0.011) and those who did not have a history of TB (AOR=0.47, 95% CI: 0.10 to 0.75, p=0.028) were more likely to have successful MDR-TB treatment outcomes.Conclusions Favourable treatment outcomes for patients with MDR-TB can be achieved in a resource-limited country. Although the recommended WHO target of ≥75% was not met, the current result (71.7% treatment success rate) is still commendable considering all the challenges associated with TB treatment in Ghana.